Unmet needs and barriers to services among people who inject drugs with HIV in the United States. Issue 4 (2nd October 2021) - Dasgupta, Sharoda; Tie, Yunfeng; Beer, Linda; Broz, Dita; Vu, Quan
Abstract: Data on use of and barriers to HIV ancillary care services among people who inject drugs (PWID) with HIV can inform interventions intended to improve access to care, but national estimates are lacking. We analyzed data on PWID with HIV from the CDC Medical Monitoring Project. Overall, 79% had an unmet need for ≥1 service. Services with the highest unmet need included: dental care (38%), drug/alcohol treatment (20%), transportation assistance (20%), and HIV peer group support (20%). Unmet needs for mental health services (13% vs. 23%) and HIV peer group support (15% vs. 29%) were lower among persons attending Ryan White HIV/AIDS Program (RWHAP)-funded facilities for HIV care. Barriers to care services varied by service type. Modeling components of the RWHAP structure in non-RWHAP funded facilities, including integration of support services and use of patient navigation services in the HIV medical care setting, may improve outcomes among PWID with HIV.